Economic incentives for soil conservation: a dinamic game model - Benito Amaro, Ignacio (International Association of Agricultural Economists, 2021)
This paper presents a theoretical model to analyze the incentives for protecting soil productivity in presence of separation of property and control in agricultural land. Using a dynamic model of contracts between the landlords and operators we analyze the incentives of different type of contracts (fixed rate contracts or sharecropping contracts) and their potential impact on soil conservation. The main research question of this paper is: do landlords and tenants have conflicting incentives regarding soil conservation? Our theoretical results are consistent with previous empirical literature that find that, depending on the contract specifications, there are no conflicting incentives.